Controls on silica enrichment of lower cambrian organic-rich shale deposits. (August 2021) - Gao, Ping; He, Zhiliang; Lash, Gary G.; Zhou, Qin; Xiao, Xianming
Abstract: The factors controlling silica enrichment of the Lower Cambrian sedimentary succession have been disputed for a long time. This paper describes results of a petrological and geochemical investigation of Lower Cambrian shale deposits of the intraplatfrom basin of the Yangtze Block, South China, with the goal of elucidating potential controls on silica enrichment of these deposits. Excess silica (Sixs ) concentrations in the studied deposits suggest that silica was generally enriched in Lower Cambrian units, including the Maidiping Formation (MDP) and the overlying Qiongzhusi Formation (QZS). Greater excess silica concentrations in the MDP relative to the QZS may reflect the influence of three factors: continental weathering, aeolian input, and biological activity. Corrected chemical index of alteration (CIAcorr ) values and Ti/Al ratios of the MDP suggest that strong chemical weathering increased the delivery of dissolved silica to the global ocean during the episodes of warm, humid paleo-climate conditions. This, in tandem with diminished aeolian input that accompanied the humid climate, favored establishment of a silica-rich ocean during Fortunian and early Stage 2 time. The presence of coeval massive chert-phosphorite deposits may be attributed to blooms of phytoplankton and siliceous organisms (mainly sponge spicules) induced by upwelling of nutrient-rich bottom waters (e.g., Si and P). However, the abundance of low-diversity sponge spicules was likely insufficient to achieve silica supersaturation of seawater by itself so that direct precipitation of aqueous silica from Si-enriched seawater and pore water may have partly contributed to silica enrichment of the MDP. Diminished CIAcorr values and elevated Ti/Al ratios of the QZS suggest the increased terrestrial and aeolian inputs into the global ocean under a relatively cool, arid paleo-climate condition during middle Stage 2 to the Stage 3 time thereby reducing aqueous silica concentrations. The present study suggests that the interaction among paleo-climate fluctuations, increased delivery of nutrients to the ocean, and redox variability was critical to the diversification of sponge spicule and the appearance of radiolarian during the Cambrian Explosion. Highlights: Fortunian to the early Stage 2 age deposits of the Yangtze Block, South China, are relatively enriched in silica. Major factors controlling the enrichment of silica of the Lower Cambrian deposits have been proposed. Early Cambrian climate fluctuations exerted considerable impact on silica enrichment and the evolution of siliceous organisms.